SINGULAR IMPLEMENTASI TWELVE TONE SERIALISM MUSIC PADA ANSAMBEL CAMPURAN - Anggara, Rama; Ismunandar, Ismunandar; Muniir, Asfar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractSingular is the title of twelve tone serialism music composition implementated on the mixed ensemble. Twelve tone serialism music is one of the the therminology idiom of western music on Twentieth Century Music era, using 12 chromatic notes which is processed with constructive dan structural. The formulation idea in the composition are implementation twelve tone matrix serialism music, the application of tone row, the harmony processing and music form. The creation stage refers to the systematic stages in the process of writing a musical work that is directly observed in musical instruments and observation some analysis results from the serialism music and some literature studies on the Twentieth Century Music era, exploration stage especially on technique of composition and also technique processing from musical instrument and evaluation phase at work process to the music player. This music creation method used composition creation approach in the creation of the composition, there are transference, syncretic, and synthesis. This work is expected to give some inovation and insight to development knowledge of especially on music Serialism Music as well as views in music composing trough the West Kalimantan traditional instrument and western instrument. Keyword: Music Composition, Serialism Music, Twelve Tone